Methane Recovery from the Inedible Portion of Mature Vigna radiata Biomass (Mung Bean) Using Anaerobic Reactor Equipped with a Solid/liquid Separation Module, and its Kinetic Analysis - Sugawara, Kazuki; Sun, Meng; Sangcharoen, Rutrawee; Toderich, Kristina; Yasui, Hidenari; Kitithammarong, Thanawat; Endo, Ryosuke; Terashima, Mitsuharu (Journal of Water and Environment Technology, 2024)
Using an inedible portion of mature mung bean biomass, methane fermentation experiments were carried out where the digestates were mechanically thickened to extend the solids retention time. The chemical analysis revealed that the conventional COD analytical method with dichromate could not perfectly oxidise the lignocellulosic compound. The measured COD was underestimated by about 10% from the elemental formulae of the biomass. In the kinetic analysis based on the IWA-ADM1 model, the enzymatic decomposition of the lignocellulosic compound limited the overall process performance, and was expressed in a first-order rate expression with 0.051 d−1 and 0.071 d−1 for the leaf fraction and the stem fraction respectively. During the continuous experiment, an unusual accumulation of soluble carbohydrates was recognised. This phenomenon was also modelled as a fragmentation of the lignocellulosic compound where very small unbiodegradable organic particles were released into the liquid. According to the steady-state calculation using the model, about 70% of the plant biomass COD could be converted to methane when the reactor was operated at the solids retention time of 100–200 days with a volumetric loading rate of 10–12 kg-COD/m3/d. The model also showed the reactor volume could be reduced by 6–7 times compared to conventional chemostat reactors.